The Challenge of Improving Evaluation in Active Learning in Health Education - Lemes, Monike Alves; Higa, Elza de Fátima Ribeiro; Marin, Maria José Sanches; Lazarini, Carlos Alberto; Ghezzi, Joyce Fernanda Soares Albino [UNESP]; Medeiros, Rodolfo de Oliveira [UNESP] (Ludomedia Unipessoal Lda, 2021)
Introduction: It is expected that, in active learning, assessment will be a modulatory tool in the student's development process, but, commonly, this is an agonizing practice for teachers and students. Goals: to identify suggestions for improving evaluative practice in active learning in undergraduate health; Methods: qualitative study, carried out through semi-structured individual interviews, with 25 professors from the Nursing and Medicine courses, in a public Higher Education Institution, in the central west region of the interior of São Paulo. The data were interpreted by the Content Analysis Technique, in the thematic modality, according to the stages Pre-analysis (organization of the data collected through successive readings), Exploration of the material (identification of the categories) and Treatment of the results: inference and interpretation (clarification of the meanings contained in the data collected and articulation between data interpretation, theoretical framework and study objectives). Results: identified three categories for improving evaluation in active health learning, being: Teacher development (pedagogical teacher training, especially in affective evaluation and better preparation to deal with relational, affective, communicational and group aspects), Adequacy of instruments and evaluation practices (standardization and implementation of evaluation instruments and adherence to more objective correction criteria) and Student orientation (means of training students about evaluation practices and their objectives, with emphasis on self-evaluation and peer evaluation). Final considerations: it is noted that the improvement of evaluative practice in active learning is inseparable from the training of teachers and students and the adoption of standardized assessment practices and instruments known to all its actors.
O desafio do aprimoramento da avaliação em aprendizagem ativa na formação em saúde
Keywords: Educational Measurement; Learning; Problem-Based Learning